Transaksi Hubungan Seksual Melalui Michat Dalam Perspektif Perundang-Undangan - Putri Salamah, Maydaria; Usman; Erwin (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2025)
The development of digital technology has created new phenomena in prostitution practices through the Michat application, raising problems of norm ambiguity and regulatory disintegration in the Indonesian legal system. Regulations regarding sexual transactions through Michat are scattered across various laws such as the Criminal Code, ITE Law, Pornography Law, TPPO Law, and TPKS Law, each with different approaches without clear harmonization, creating legal uncertainty for law enforcement officers and society. This research uses normative legal methods with statutory, conceptual, and case approaches to analyze the harmonization of regulations and law enforcement regarding sexual transactions through Michat. The research results show significant disharmonization in laws related to sexual transactions through Michat, where this regulatory disintegration creates norm overlaps, inconsistent article application, and legal uncertainty reflected in concrete cases in Surabaya (2024) and Mamuju (2023) which used different legal bases for similar cases. The research concludes that legislative harmonization becomes an urgent need to create alignment, consistency, and legal certainty in the national legislative system to provide optimal protection for victims and effective law enforcement against digital technology-based crimes